Can flexible ureteroscopy using flexible and navigable suction ureteral access sheath (FANS-UAS) minimize postoperative double J stent placement? Results from a propensity score-matched analysis of 540 patients of the European Association of Urology Section of Endourology and global FANS collaborative study group - Daniele Castellani; Bhaskar Kumar Somani; Khi Yung Fong; Steffi Kar Kei Yuen; Chin Tiong Heng; Mohamed Elshazly; Karl Tan; Thomas R. W. Herrmann; Olivier Traxer; Vineet Gauhar (Investigative and Clinical Urology)
Purpose: To evaluate whether using flexible and navigable suction ureteral access sheath can obviate insertion of double J stent and establish the safety of overnight ureteric catheter placement as alternative following flexible ureteroscopy for kidney stones. Materials and Methods: Five hundred forty adults were prospectively enrolled across 25 centers (from April 2023 to January 2024). Patients were divided into group 1 (overnight ureteric catheter), and group 2 (double J stent). Surgeons could choose either modality as per their discretion. One-to-one propensity score-matching for age, sex, pre-stenting, Hounsfield units, stone volume and location was performed. Thirty-day computed tomography scan was done to estimate stone-free status. Results: After matching, 120 patients were included in each group. Group 1 had significantly shorter lasing, ureteroscopy, surgical time. Median day 1 loin pain score was similar (1 [1, 2] in both groups). Median postoperative stay was shorter in group 1 (0 days [0, 1] vs. 1 day [0, 2], p<0.001). One patient in group 2 required a blood transfusion. Incidence of fever was similar (5.0% vs. 0.8%). Loin/abdominal pain requiring medication occurred in one patient in group 2. Stent-related symptoms occurred in 2 patients in group 1. Three patients (2.5%) in group 1 and 2 patients (1.7%) in group 2 required readmission. Thirty-day stone-free status was higher in group 1 patients (79.2% vs. 56.7%). Conclusions: In selected patients after thorough inspection to ensure no injury or residual fragments remain, placing an overnight ureteric catheter can be a safe alternative to a double J stent.